Administrative Control over Local Government (A Study of Determination of 2014 Kediri Regency Budget) - Muluk, Mujibur Rahman Khairul; Solikin, M (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Central government control over local government is necessary In order to ensure achievement of decentralization policy goals. Unfortunately, study about local government control is uncommon in Indonesia. This study aims to describe types of central government control to local government and to explain how those control work in crucial political situation within local government. Most of problematic LGR (Local Government Regulation) were about local government budget. Similar to the problem that was faced by many local governments in Indonesia, Kediri Regency struggle with delay of determination of local government budget. This qualitative research was conducted in 2014-2015 in approval process of 2014 Kediri Regency Budget. McNabb procedures for data analysis (2002) was used in this research. There are three types of administrative control: general, sectoral, and functional control. Another research findings about the cause of determination delay for LGR about 2014 local government budget (APBD) were two things. First source of problem was conflict within and between Kediri Regency Council and Local Government. Second source of problem was lack of control from central government about the overtime budget approval.Â Â Â